PENGGUNAAN BAHAN AJAR STRUKTUR ALJABAR UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIS PADA MAHASISWA IKIP PGRI PONTIANAK - Jamilah, Jamilah; Fadillah, Syarifah (Jurnal Pendidikan Matematika dan IPA, 2017)
This study aims to know the effect of teaching and learning using Algebraic Stucture materials based on mathematical proof to improve mathematical proof ability. The type of this study is experimental method with One Shot Case Study design. Population in this study is students of 6th semester in Departement of Mathematics Education and sample is students in class A and B which are consist of 83 students. The results show that teaching and learning using Algebraic Structure materials based on mathematical proof can improve mathematical proof ability with 16Z0bs=9,74>1,645=Z0,05"> . The total score of mathematical proof ability is 44,34 from 100 or 44,34 % (good). In each aspect, teaching and learning using Algebraic Stucture materials based on mathematical Proof can improve the ability to construct evidence includes the use of methods of proof and the use of fact, the concept and principles of mathematics by 26,99 from 50 or 53,98 % (good) and 17,14 from 50 or 34,70 % (good) in the aspect of the ability to read a proof to determine truth or mistake by seeing the correspondence between the system of axioms, premises, or theorems existing.Â Keywords : algebraic structure material, mathematical proof ability